Marxism, Communism, Marxian Socio-political Economic Theory and the Socialist World - Sehgal, M. L. (Advances in Social Sciences Research Journal, 2020)
Marxian model of economic, as enunciated in "Das-Capital" disapproved of the two classical models of economics proposed by Adam Smith and John Maynard Keynes though both had stood the test of the time. Marx’s Economic Theory encompassed the social, historical, and economic points of view based upon the thesis of Hegel's philosophy as well as its antithesis. Marx believed that the concept of relations of production as proposed by Capitalism was vague for the socio-cultural set up of a society. He said that Capitalism would not end up in a quiet death; rather it would have to be broken up with a 'Bang'; maybe by Violent Revolution. Rather than giving some weightage to machines, the paper, or the ’capital’, Marx would put all his eggs on the ‘Labor Class’ as he opined that the ‘Capitalist Class’ exploits the Labor Class. He would proclaim that the sole factor which decided the prices of the commodities was the value of the labor as determined by Labor Theory of Value (LTV) and not by the cost of machines and the capital put in for running the various operation of the establishment. There would be no Ownership of property; State becoming the sole proprietor as everything will be nationalized. Countries like the USSR and East Germany, after being separated from West Germany, because of the execution of treaties of WW-II (1945). North Vietnam, North Korea, Cuba, and Venezuela also turned Socialists. Their economies (GDPs) will make a part of the present study. Poland, Czechoslovakia, Hungry, and China, which also followed the Socialistic pattern, are excluded.